Effects of White Noise and Holding on Pain Perception in Newborns - KARAKOÇ, AYŞE (ELSEVIER SCIENCE INC, 2014)
This experimental study on newborns was conducted to compare the effects of various atraumatic care procedures during an infant's crying response to pain. Included in this study were 120 newborns chosen from among healthy infants admitted to the Obstetrics Department of Canakkale State Hospital between April 2010 and June 2010. The patients were divided into three physically homogeneous groups. Infants in group 1 were held on the mothers' laps, infants in group 2 were held on the mother's laps and listened to white noise, and infants in group 3 lay in their cribs and listened to white noise while undergoing a painful procedure. Data collection included the Neonatal Infant Pain Scale, which was used to evaluate the behavioral responses to pain during a heel prick blood draw and a newborn information sheet developed by the researcher. Changes in cardiac and respiratory rates recorded during the invasive procedure were statistically significant among the three groups (p < .05). The shortest crying period and the lowest behavioral reactions were among those infants lying in their cribs and listening to white noise. This group was then followed by the infants who listened to white noise while being held by their mothers. The highest behavioral reaction was reported by those infants who were held by their mothers but did not listen to white noise. According to the results, white noise is an effective nonpharmacologic method to control pain, reduce crying time, and positively effect vital signs. Therefore, it is recommended that the use of white noise be practiced on newborns when they undergo painful procedures. (C) 2014 by the American Society for Pain Management Nursing
Keywords: PROCEDURAL PAIN; PREVENTION; CARE